Ly6Chi Monocytes and Their Macrophage Descendants Regulate Neutrophil Function and Clearance in Acetaminophen-Induced Liver Injury - Graubardt, Nadine; Vugman, Milena; Mouhadeb, Odelia; Caliari, Gabriele; Pasmanik-Chor, Metsada; Reuveni, Debby; Zigmond, Ehud; Brazowski, Eli; David, Eyal; Chappell-Maor, Lousie; Jung, Steffen; Varol, Chen (Frontiers in Immunology, 2017)
Monocyte-derived macrophages play a pivotal role in the resolution of Acetaminophen-Induced Liver Injury (AILI). Timely termination of neutrophil activity and their clearance are essential for liver regeneration following injury. Here, we show that infiltrating Ly6Chi monocytes, their macrophage descendants, and neutrophils spatially and temporally overlap in the centrilobular necrotic areas during the necro-inflammatory and resolution phases of AILI. At the necro-inflammatory phase, inducible ablation of circulating Ly6Chi monocytes resulted in reduced numbers and fractions of Reactive Oxygen Species (ROS)-producing neutrophils. In alignment with this, neutrophils sorted from monocyte-deficient livers exhibited reduced expression of NADPH Oxidase 2. Moreover, human CD14+ monocytes stimulated with LPS or hepatocyte apoptotic bodies directly induced ROS production by co-cultured neutrophils. RNA-seq-based transcriptom profiling of neutrophils from Ly6Chi monocyte-deficient versus normal livers revealed 449 genes that were differentially expressed with at least two-fold change (p ≤ 0.05). In the absence of Ly6Chi monocytes, neutrophils displayed gene expression alterations associated with decreased innate immune activity and increased cell survival. At the early resolution phase, Ly6Chi monocytes differentiated into ephemeral Ly6Clo monocyte-derived macrophages (MoMF) and their absence resulted in significant accumulation of late apoptotic neutrophils. Further gene expression analysis revealed the induced expression of specific repertoire of bridging molecules and receptors involved with apoptotic cell clearance during the transition from Ly6Chi monocytes to MoMF. Collectively, our findings establish a phase-dependent task division between liver-infiltrating Ly6Chi monocytes and their MoMF descendants with the former regulating innate immune functions and cell survival of neutrophils and the later neutrophil clearance.